2006
DOI: 10.1038/sj.cr.7310083
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with autologous T cells enhances in vivo anti-tumor immune responses accompanied by up-regulation of GADD45β

Abstract: Immunization with inactivated autoreactive T cells may induce idiotype anti-idiotypic reactions to deplete autoreactive T cells, which are involved in autoimmune diseases. However, it is unknown whether attenuated activated healthy autologous T-cell immunization could increase anti-tumor immune responses. To this end, C57Bl/6 mice were immunized with attenuated activated autologous T cells. The splenocytes from immunized mice showed a higher proliferative ability than that from naive mice. The special phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…The serum samples were tested in duplicate for the production of IFNγ, IL-12, TNFα and IL-10 using ELISA kits (R&D). In this assay, the IL-12 level was significantly increased in the immunized mice as we reported before (p = 0.0057) [35]. Th1 cytokines IFNγ and TNFα increased significantly also in immunized mice than those from naïve mice (p = 0.047 and 0.021 respectively).…”
Section: Enhancement Of Ifnγ and Il-12 Production In Immunized Micesupporting
confidence: 68%
See 2 more Smart Citations
“…The serum samples were tested in duplicate for the production of IFNγ, IL-12, TNFα and IL-10 using ELISA kits (R&D). In this assay, the IL-12 level was significantly increased in the immunized mice as we reported before (p = 0.0057) [35]. Th1 cytokines IFNγ and TNFα increased significantly also in immunized mice than those from naïve mice (p = 0.047 and 0.021 respectively).…”
Section: Enhancement Of Ifnγ and Il-12 Production In Immunized Micesupporting
confidence: 68%
“…In our previous work, we reported that administration with irradiated, activated autologous T cells in mice evokes anti-tumor immunity by enhancing the survival of activating T cells, which is accompanied by GADD45b upregulation in T cells [35]. In this report, we further investigated the anti-tumor mechanisms elicited by activated autologous T immunization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, alternative strategies potentially leading to cancer eradication or regression in animal or clinical models are being enthusiastically pursued. In this issue of Cell Research, Wang et al report a novel way to induce tumor immunity by the use of irradiated autologous T cells [5].In their protocol, Wang et al isolated activated T cells from C57BL/6 mouse splenocytes stimulated in vitro. These cells were then irradiated at 30 Gy and injected intraperitoneally into syngeneic mice every 5 days.…”
mentioning
confidence: 99%
“…Currently, alternative strategies potentially leading to cancer eradication or regression in animal or clinical models are being enthusiastically pursued. In this issue of Cell Research, Wang et al report a novel way to induce tumor immunity by the use of irradiated autologous T cells [5].…”
mentioning
confidence: 99%